1996
DOI: 10.1021/cm960056l
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Materials Generated by High-Intensity Ultrasound:  Sonochemical Synthesis and Catalytic Studies

Abstract: The sonochemical decomposition of volatile organometallic compounds produces high surface area solids that consist of agglomerates of nanometer clusters. For iron pentacarbonyl and tricarbonylnitrosylcobalt, nanostructured metals and alloys are formed; for molybdenum hexacarbonyl, the metal carbide is produced. These sonochemically produced nanostructured solids are active heterogeneous catalysts for hydrocarbon re-forming and CO hydrogenation. The sonochemical synthesis, characterization, and catalytic studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
161
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(164 citation statements)
references
References 41 publications
2
161
0
1
Order By: Relevance
“…Recently, sonication has been applied in the synthesis of novel nanomaterials in aqueous solutions. 9,10 The chemical effect of ultrasound originates from the formation of ultrasonic cavitation, with the growth and collapse of microbubbles in the liquid phase generating very high temperatures and pressures followed by rapid cooling. These extreme conditions have been exploited for the preparation of nanoparticulate metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, sonication has been applied in the synthesis of novel nanomaterials in aqueous solutions. 9,10 The chemical effect of ultrasound originates from the formation of ultrasonic cavitation, with the growth and collapse of microbubbles in the liquid phase generating very high temperatures and pressures followed by rapid cooling. These extreme conditions have been exploited for the preparation of nanoparticulate metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology and size of the particles are greatly affected by the conditions used for fabrication: temperature and calcination rate in the thermal decomposition method; conditions of gel preparation such as pH, gelling agents, heating rate for gel formation and calcination temperature of the gels in the sol-gel method. Recent studies have shown sono-chemical acceleration of chemical effects involved in the synthesis of novel nanomaterials in aqueous solutions (Kenneth and Price, 1999;Bhatte et al, 2011;Suslick et al, 1996). Chemical effects of ultra-sound originate from the formation of ultrasonic cavitation, the growth and collapse of microbubbles in the liquid phase generating very high temperatures and pressures followed by rapid cooling.…”
Section: Introductionmentioning
confidence: 99%
“…MALDI spectra show that the Mo 13 -containing peaks are present, whereas intensities of all the other small clusters, which were shown up in LDI analysis, fade or even vanish. The preferential enhancement in the Mo 13 peaks suggested that a molecular entity could be existing in the sample. It may be noted that the Mo 13 peak is stronger than those of the neighboring clusters.…”
Section: Resultsmentioning
confidence: 99%
“…Nano forms of these materials have their own advantages over the corresponding bulk materials. Electrochemical deposition [12] and sonochemical routes [13,14] are some other methods adapted for the synthesis of nanostructured materials. Electrochemical methods result in the formation of nanomaterials as a film, whereas sonochemical methods produce free-standing nanoflakes of metal chalcogenides with controlled size.…”
mentioning
confidence: 99%